2020
DOI: 10.1111/1462-2920.14888
|View full text |Cite
|
Sign up to set email alerts
|

Chromobacterium violaceum delivers violacein, a hydrophobic antibiotic, to other microbes in membrane vesicles

Abstract: This study describes Chromobacterium violaceum's use of extracellular membrane vesicles (MVs) to both solubilize and transport violacein to other microorganisms. Violacein is a hydrophobic bisindole with known antibiotic activities against other microorganisms. Characterization of the MVs found they carried more violacein than protein (1.37 AE 0.19-fold), suggesting they may act as a reservoir for this compound. However, MVs are not produced in response to violaceina ΔvioA isogenic mutant, which is incapable o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
54
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 38 publications
0
54
0
3
Order By: Relevance
“…Infection of this bacterium in humans occurs through exposure of open wounds in contact with the waters of streams, rivers and lakes, and also in contaminated soil (Thwe, Ortiz, & Wankewicz, 2020). Studies on violacein, a violet-colored substance, have shown effective effects against several bacteria, especially gram-positive ones, even combating multidrug-resistant strains of Staphylococcus aureus (Choi, Lim, Cho, & Mitchell, 2020). Violacein is detected in several environments and its role should be widespread regarding habitats and microorganisms (Choi, Yoon, Lee, & Mitchell, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Infection of this bacterium in humans occurs through exposure of open wounds in contact with the waters of streams, rivers and lakes, and also in contaminated soil (Thwe, Ortiz, & Wankewicz, 2020). Studies on violacein, a violet-colored substance, have shown effective effects against several bacteria, especially gram-positive ones, even combating multidrug-resistant strains of Staphylococcus aureus (Choi, Lim, Cho, & Mitchell, 2020). Violacein is detected in several environments and its role should be widespread regarding habitats and microorganisms (Choi, Yoon, Lee, & Mitchell, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Viol is released from bacteria via membrane vesicles. 1 Several potential clinical uses of Viol are described in the literature such as microbiocide activity targeting the cytoplasmic membrane of Gram-positive microorganisms, 2,3 antiplasmodial and trypanocidal, 4 analgesic, 5 antitumoral and virucide among others recently reviewed. 6 Additionally, Viol was reported as an immunostimulatory molecule that is mediated by TLR8 and relevant for immunosuppressed patients.…”
Section: Introductionmentioning
confidence: 99%
“…When incubating S. aureus with purified violacein, OMVs from C. violaceum or from mutants unable to produce violacein, they found that S. aureus was killed by purified violacein or violacein solubilized by OMVs. Based on these results, the researchers hypothesised that C. violaceum produces violacein, which is packed into OMVs, and secretes the OMVs into the environment where they eventually encounter S. aureus cells leading to their growth inhibition (Choi et al ., ).…”
mentioning
confidence: 97%
“…These OMVs represent the only available shuttle for C. violaceum to secrete a toxic hydrophobic compound into the environment, where its role would be that of inhibiting the growth of competitors. However, C. violacein still secretes OMVs although it is not producing violacein indicating that violacein production is not a trigger for OMV secretion (Choi et al ., ). This raises the question of what the general function of OMVs in this bacterium might be.…”
mentioning
confidence: 97%
See 1 more Smart Citation